Mutual impedance of axially-symmetric modes of a circular plate - RDZANEK, Witold (Archives of Acoustics, 1986)
This paper presents an exact calculation of the mutual radiation impedance of axially-symmetric modes of a fixed at the edge circular plate. Linear and harmonic processes in respect to time have been considered and it has been accepted that the plate radiates acoustic waves into a lossless gas medium. Included here expressions for the mutual impedance in the form of single integrals have been adopted on the basis of several simplifying assumptions to numerical calculations for low and high frequencies of radiated waves. Achieved results are used in the analysis of the impedance and sound power radiated by a circular plate excited to vibrate by a known (from the assumption) superficial distribution of the exciting force.